1990
DOI: 10.1111/j.1532-5415.1990.tb03492.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training in the Elderly on the Occurrence and Time to Onset of Cardiovascular Diagnoses

Abstract: To examine the long-term effects of aerobic exercise on the occurrence and time to onset of cardiovascular diagnoses, 184 initially healthy older subjects were randomized into either a long-term exercise group (Group A, n = 80), a short-term exercise group (Group B, n = 42), or a contract control group (Group C, n = 62). After completion of two years in the study, data on new cardiovascular diagnoses and time to onset of these diagnoses in each of the three groups were compared. The occurrence rates for new on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 22 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…We have shown that our exercise subjects not only exhibited the physiologic changes we have described here, including a 20% increase in training work rate, but also exhibited, over the two years following training, a significant reduction in new‐onset cardiovascular diagnoses compared to our control subjects. This was true not only of a group that trained during the entire 2 years, but also of a subgroup that stopped after the 4‐months program herein described 30 …”
Section: Discussionmentioning
confidence: 75%
“…We have shown that our exercise subjects not only exhibited the physiologic changes we have described here, including a 20% increase in training work rate, but also exhibited, over the two years following training, a significant reduction in new‐onset cardiovascular diagnoses compared to our control subjects. This was true not only of a group that trained during the entire 2 years, but also of a subgroup that stopped after the 4‐months program herein described 30 …”
Section: Discussionmentioning
confidence: 75%
“…While we did not obtain a similar result, Donahue et al7 had a younger population, longer follow-up, more rigorous measure of activity, and more complete and objective ascertainment of coronary events. Studies with stronger designs generally show larger benefits associatedwith physical activity.I Posner et al 26 found a lower occurrence and delayed onset of cardiovascular diagnoses in elderly participants in an exercise program vs nonexercising controls over 2 years; however, the major difference occurred in the development of arrhythmias.…”
Section: Outcomes After 6 Yearsmentioning
confidence: 97%
“…Many studies report that aerobic exercise improves aerobic capacity in older adults (1,4,9,10,14,17,21,33,35,39,41,48,53,61,69,70,73,79,81,84,91,93). Improvement with 3-12 months of exercise is modest and ranges from 5% to 20%.…”
Section: Effects Of Exercisementioning
confidence: 99%